P486 Treatment-emergent COVID-19 infections in ozanimod ulcerative colitis and multiple sclerosis clinical trials. (21st January 2022) - Ungaro, R; Siegel, C A; Cree, B A C; Selmaj, K W; Ahmad, H A; Pai, A; Ather, S; Henry, A; Charles, L; Petersen, A; Cheng, C Y; Afsari, S; et al.
Abstract: Background: Ozanimod, a sphingosine 1-phosphate (S1P) receptor S1P1 and S1P5 modulator, is approved in the United States for moderately to severely active ulcerative colitis (UC) and in multiple countries for relapsing multiple sclerosis (MS). We describe COVID-19 outcomes in ozanimod-treated UC or MS patients (pts) in active phase 3 open-label extension (OLE) studies. Methods: A database search identified COVID-19 infection reports in ozanimod-treated pts with UC in the True North OLE and MS in the DAYBREAK OLE. The analysis period was November 1, 2019 to either August 31, 2021 (UC) or May 10, 2021 (MS). The last COVID-19 event from all pts with ≥1 event was analyzed. Results: Among 2792 ozanimod-treated pts with UC or MS, 258 developed COVID-19 (confirmed: 215); thus, the incidence in these clinical trial settings was 9.2% during the analysis periods. Most pts with confirmed cases (193/215 [89.8%]) had nonserious infections not requiring hospitalization or meeting other International Conference on Harmonisation criteria for a serious event. Of 611 ozanimod-treated pts with UC, 68 (11.1%) developed COVID-19 (confirmed: 55; Fig 1 ). A majority of UC pts with confirmed cases (45/55 [81.8%]) had nonserious COVID-19; most (54/55 [98.2%]) recovered (2 with sequalae) and 1 was recovering at data cutoff. One UC pt with confirmed COVID-19 discontinued ozanimod (1.8%), 23 temporarily interrupted it (41.8%), and 31 had no change to treatment (56.4%). No COVID-19‒related deaths were reported in UC pts. Of 2181 ozanimod-treated pts with MS, 190 (8.7%) developed COVID-19 (confirmed: 160; Fig 2 ). Most MS pts with confirmed COVID-19 (148/160 [92.5%]) had nonserious cases; most (158/160 [98.8%]) recovered (5 with sequelae) (Fig 1 ). No MS pts with confirmed cases discontinued ozanimod, 61 temporarily interrupted it (38.1%), and 99 had no change to treatment (61.9%). Outcomes in 13 additional UC pts (Fig 1 ) and 30 additional MS pts (Fig 2 ) with suspected COVID-19 were similar to those with confirmed cases. There were 3 COVID-19‒related deaths in the MS program. One pt died from a presumed pulmonary embolism; this pt had received high-dose corticosteroids for MS relapse immediately before COVID-19 symptom onset. Another pt died from suspected COVID-19‒related respiratory failure. One tetraplegic, cachectic pt died from a lung abscess following COVID-19 infection. Conclusion: In the UC and MS OLE studies, most pts with confirmed COVID-19 had nonserious infections, recovered, and did not require ozanimod discontinuation. There were 3 deaths in MS patients (case-fatality rate 1.6% in MS, 1.2% overall).